Influence of the thermomechanical properties on the joining of adhesion incompatible polymers by form-fit using the vibration welding process - M. Wolf; S. Hertle; D. Drummer (eXPRESS Polymer Letters, 2019)
In the product manufacturing cycle, the joining of polymers often takes a central position. Vibration welding is characterized by short cycle times, high process flexibility and stability as well as by the achievement of high bond strengths without using additives. However, the vibration welding process is clearly restricted by a necessary adhesion compatibility of the joining partners. By means of structuring one joining partner and subsequent filling of the structures by a second joining partner, the joining by form-fit using vibration welding enables the combination of adhesion incompatible polymers. Within these investigations, bonds between adhesion incompatible semi-crystalline thermoplastics were generated based on mechanical adhesion. Also semi-crystalline and amorphous polymers could be connected for the first time without any connecting elements, although they conventionally do not show mechanical resilience. The analysis of the thermomechanical material properties and the resulting multimaterial link enabled the determination of first influences on the resulting formfit connection caused by the occurring joining zone temperature.